Sequential organization in the song of thrush nightingale (Luscinia luscinia): clustering and sequential order of the song types. Issue 2 (4th May 2017) - Ivanitskii, V. V.; Marova, I. M.; Antipov, V. A.
Abstract: Sequential organization (or syntax) is widely recognized as one of the most intriguing traits of avian song. We examined the singing of thrush nightingale ( Luscinia luscinia ) with emphasis on the clustering and sequencing of different song types. The individual repertoire size averaged 12.2 ± 3.7 song types (range 7–23 song types). The song types most common in the population were mutually associated within individual repertoires in non-random combinations. The vast majority of transitions between these song types were predominantly unidirectional. During singing, different song types were mutually associated in the fixed vocal programmes. Each programme was composed of 2–6 song types, which were usually delivered in a relatively fixed order. The compositions of some programmes were found to be identical across the whole of Moscow and even far outside it. We suggest that, during song learning, thrush nightingales memorize the programme not as a set of separate song types but as a unitary vocal pattern. Most frequently, the performance of the programs started from the very beginning. The number of complete and incomplete renditions that began from initial song types exceeded considerably the number of renditions that began from any intermediate song types. In the conclusion, we discuss some differences and similarities between song systems of the thrush and common nightingale ( Luscinia megarhynchos ).